2020
DOI: 10.1155/2020/8504238
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MicroRNA‐16 Alleviates Atherosclerosis by Inhibition of Inflammatory Pathways

Abstract: Background. Our previous study demonstrated that the expression of miR-16 was downregulated in the cell and animal models of atherosclerosis (AS), a main contributor to coronary artery disease (CAD). Overexpression of miR-16 inhibited the formation of foam cells by exerting anti-inflammatory roles. These findings indicated miR-16 may be an anti-atherogenic and CAD miRNA. The goal of this study was to further validate the expression of miR-16 in CAD patients and explore its therapeutic roles in an AS animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Forced overexpression of circZNF609 has enhanced production of inflammatory cytokines IL-6 and TNF-α, while enhancing expression of IL-10. These effects are possibly mediated through sponging miRNAs ( 66 ). In an eminent study, Guo et al ( 67 ) have assessed levels of hsa_circ_0002984, hsa_circ_0010283, and hsa_circ_0029589 in human peripheral blood mononuclear cell–originated macrophages from CAD patients and evaluated the consequences of overexpression or silencing of these circRNAs.…”
Section: Circrnas and Cadmentioning
confidence: 99%
See 1 more Smart Citation
“…Forced overexpression of circZNF609 has enhanced production of inflammatory cytokines IL-6 and TNF-α, while enhancing expression of IL-10. These effects are possibly mediated through sponging miRNAs ( 66 ). In an eminent study, Guo et al ( 67 ) have assessed levels of hsa_circ_0002984, hsa_circ_0010283, and hsa_circ_0029589 in human peripheral blood mononuclear cell–originated macrophages from CAD patients and evaluated the consequences of overexpression or silencing of these circRNAs.…”
Section: Circrnas and Cadmentioning
confidence: 99%
“…Expression of circZNF609 has been shown to be reduced in peripheral blood leukocytes of CAD patients in correlation with levels of CRP and lymphocyte counts. In addition, down-regulation of circZNF609 has been associated with higher risks of CAD with accuracy of 0.761 ( 66 ). In a high-throughput circRNA profiling, Zhang et al have demonstrated differential expression of 22 circRNAs between CAD patients and healthy subjects.…”
Section: Circrnas and Cadmentioning
confidence: 99%
“…Several theories have been proposed to explain the pathogenesis of atherosclerosis and in the particular inflammatory response, however, the detailed mechanisms of inflammation in atherosclerosis development have not been fully clarified, and effective diagnostic and therapeutic approaches remain limited. Studies demonstrated that the expression of miR-16 was downregulated in the cell and animal models of atherosclerosis, as the main contributor to CAD, thus these findings suggest, that the miR-16 gene from miR-16 microRNA precursor’s family may be a potential diagnostic biomarker and therapeutic target for atherosclerosis anti-inflammatory therapy [ 161 , 162 ].…”
Section: Cardio Effectsmentioning
confidence: 99%
“…More recently, in vivo studies demonstrated that injection of miR-16 agomiR into ApoE −/− mice reduces the formation of atherosclerotic plaques and inhibits the proinflammatory cytokines, including IL-6, TNF-α, MCP-1, and IL-1β, in the plasma and tissues, but promotes the secretion of anti-inflammatory factors, including IL-10 and TGF-β. They found that miR-16 might downregulate target program cell death 4 (PDCD4) to activate p38 and ERK1/2 and inactivate the JNK pathway [67]. However, these reports suggest that inhibition of individual inflammatory cytokines is not enough to be effective in treating atherosclerosis.…”
Section: Inflammation and Endmt In Atherosclerosismentioning
confidence: 99%